How green is our future? Thor Chemicals: a case study in South African environmental policy - Flint, Adrian (Rhodes University, Faculty of Humanities, Department of Political Studies, 1998)
This study focuses on South African Environmefltal policy; in particular its policies regarding hazardous waste. These policies are addressed within the framework of a case study which serves as basis to critically evaluate government environmental policies both past and present. The thesis examines South African environmental policy against the backdrop of competing schools of thought regarding the relationship between growth and development on the one hand and long term environmental security on the other. Development strategies such as Sustainable Development and the government's Growth, Employment and Redistribution as well as philosophies such as Deep Ecology will be discussed. The thesis argues that Non-Governmental Organisations are the holders of a real environmental ethic and thus their role in preventing environmental degradation is of critical importance. Furthermore, it is imperative that this ethic be disseminated across society if South Africa is to successfully pursue sound environmental policies. This argument is pursued by way of a case study, Thor Chemicals: a company responsible for the running of the largest mercury recovery facility in the world. This plant, which operated in Cato Ridge, KwaZulu-Natal, has been the source of much controversy since it was found that many of its employees and ex-employees were suffering from severe mercury poisoning resulting in two fatalities. The company was also involved in the importation of hazardous wastes as well as the pollution of the surrounding environment. Thor is currently the subject of inquiry by the government-appointed Davis Commission. It is pointed out that ill the past South Africa held no real environmental ethic and environmental degradation ensued as a result. The presented thesis argues that, despite assurances to the contrary, the present government is also without a true environmental ethic that will be effective in preventing future degradation.
Keywords: Environmental ethics|Environmental policy -- South Africa|Environmental policy -- South Africa -- Case studies|Environmental degradation -- South Africa